Pelembagaan Participatory Poverty Assessment Sebagai Strategi Pengentasan Kemiskinan di Samigaluh Kabupaten Kulonprogo - AWANG DARUMURTI (Jurnal Studi Pemerintahan, 2011)
This article try to analysis strategy for reducing poverty in Samigaluh Municapy, Kulonprogo Regionby using Participatory Poverty Assessment (PPA) strategy. PPA known as strategy to reduce povertyby including poor people to find solution of their poverty problem. In Other word, this strategy usebottom up method to reduce poverty. In Samigaluh, Poverty condition clearly seen as so many peoplelive in near poor condition. This research use qualitative approach and data collect technic useinterview and observation. From the research is gotten data that poor condition in Samigaluh causedby economic aspect, uncapability, isolation condition. PPA strategy, which is including poor people insolution making, give result that we must do some activities. The Activities are womenempowernment, Informal institution empowernment, Increase Education, Training, and so on.